New ways in therapy of abnormal uterine bleedings related to adenomyosis - N N Rukhliada; E I Biriukova; M A Melnikova; D M Gasimova (IP Berlin A.V., 2015)
The purpose of research was a comparison of the effect of a three-phase combined oral contraceptive (COC) containing estradiol valerate and dienogest in dynamic mode and single agent containing dienogest, to reduce menstrual blood loss on the background of adenomyosis.Materials and methods. Women aged 18-50 years, with a diagnosis of adenomyosis and pain hospitalized for abnormal uterine bleeding. Hysteroscopy and curettage of the uterus were performed on all the patientsw. After discharge, and the results of histological examination, patients of group 1 (no need of hormonal contraception), dienogest monotherapy was administered at a dose of 2 mg per day continuously for 6 months. Group 2 patients (who needed effective contraception) were administered three-phase COCs containing estradiol valerate and dienogest (2 days 3 mg estradiol valerate, 5 days estradiol valerate 2 mg/2 mg dienogest, 17 days estradiol valerate 2 mg/3 mg dienogest, 2 day 1 mg estradiol valerate and 2 days of placebo); 3 groip patients (not need for contraception) were treated with antifibrinolytic drug tranexamic acid at a dose of 1000 mg per day orally. Evaluates the performance of blood coagulation.Conclusions. Against the background of monotherapy a significant and reliable reduction of menstrual blood loss and the severity of pain was shown that demonstrates its effectiveness in the treatment of abnormal uterine bleeding associated with adenomyosis.